Faktor Risiko Fisiologis Penyebab Kejadian Infeksi Saluran Pernafasan Akut (ISPA) pada Balita: Literatur Riview - Syaikhah Fathinah Ridwan; Wasis Rohima; Wahyu Sudarsono; Siti Amanah Septina; Sylvia Rianissa Putri (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Acute respiratory infection (ARI) caused by environment factor, socio -demographic characteristics of parents and child physiological factors. The ARI is the top ten communicable diseases among children under five years in Indonesia. Studies of combination of two or three factors affected the ARI have reported, but study of association subs physiological factors are rarely. The aim of study was to know effect of sub physiological factors on ARI among children under five years. The study used articles from 2015-2020 and conducted from the PubMed and SCOPUS. There were 18 articles relevant with inclusion criteria in this study. Qualitative analysis was used for design study. The five physiological sub-factors, namely age, gender, exclusive breastfeeding, low birth weight (LBW), and nutritional status was associated with ARI among children under five years. The Age, exclusive breastfeeding, LBW, and nutritional status have the same impact affecting maturation immune system in infants. Larger amount testosterone hormone in male infant and smaller size of thymus than female infant. Both of them caused male infant more susceptibility affected by ARI than female infantKeywords: ARI, physiological risk factors, children under five years, gender, immune system